La biblioteca y el parlamento - Buñuel Adán, Marta (Revista General de Información y Documentación, 2002)
The aim of the present work is to describe the functions and practical tasks performed by the bibliographic information section of the Senate Library, as an example of a Second Chamber parliamentary library.
Keywords: Parliament library; Senate Library; bibliographic information; reference section